Caregiving consequences in cancer family caregivers: a narrative review of qualitative studies - Rezaei, Masoud; Keyvanloo Shahrestanaki, Sahar; Mohammadzadeh, Razieh; Aghili, Mohammad Sadegh; Rajabi, MohammadReza; Abbasi, Mohammad; Khachian, Alice; Momen, Reza; Khavassi, Mohammad; Aghaei, Simin (Frontiers in Public Health, 2024)
Cancer is a significant public health issue, causing various challenges for individuals affected by it. As cancer progresses, patients often become dependent on others for support. Family caregivers and members play a crucial role in the recovery and rehabilitation of these patients. However, caregivers themselves face numerous challenges throughout the course of their family member's illness. Exploring the experiences of family caregivers can inform long-term planning and supportive interventions to address their caregiving difficulties. This study reviews previous literature on caregiving outcomes.